Progression of Uterine Artery Pseudoaneurysm Documented by Ultrasonography: A Case Report - Qiang KK; Song QY (Dove Medical Press, 2024)
Kun-Kun Qiang,1,2 Qing-Yun Song1,2 1Department of Diagnostic Ultrasound, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Obstetric & Gynecologic and Pediatric Diseases and Birth Defects of Ministry of Education, Chengdu, People's Republic of ChinaCorrespondence: Qing-Yun Song, Department of Diagnostic Ultrasound, West China Second University Hospital, Sichuan University, Chengdu, Sichuan Province, 610041, People's Republic of China, Email huaxi2chaoshengsqy@163.comIntroduction: Uterine artery pseudoaneurysm (UAP) is a rare cause of late postpartum hemorrhage. Insufficient understanding of this condition among clinicians may result in delayed diagnosis and treatment, potentially leading to incorrect interventions and poor prognosis, including fatal hemorrhage and even necessitating hysterectomy in severe cases.Case Report: The patient, a 41-year-old woman with a history of three pregnancies and two deliveries, underwent cesarean section and subsequently experienced persistent small amounts of vaginal bleeding for a duration of two months. Transvaginal ultrasonography revealed a hypoechoic mass in the cervix that was initially misdiagnosed as a cervical fibroid. Approximately 12 h prior to admission, she experienced an episode of acute vaginal bleeding of significant intensity. Emergency transvaginal ultrasound demonstrated an intrauterine mass located in the posterior wall of the cervix with swirling blood flow, exhibiting a to-and-fro pattern. The mass was connected to the left uterine artery adjacent to the cervix through a tear measuring approximately 0.5 cm in diameter. Emergency bilateral uterine artery embolization was performed. After a follow-up period of ten months, there was no recurrence of abnormal vaginal bleeding, and subsequent ultrasound examination confirmed the complete resolution of the cervical lesions.Conclusion: The findings of this case suggest that the UAP undergoes a dynamic process. In the early stages, the lesion may manifest as a small hypoechoic or anechoic area within the myometrium. Color Doppler imaging might not reveal blood flow signals within the lesion, potentially leading to misdiagnosis as other common uterine lesions such as fibroids or cysts. However, considering the close association between UAP and the uterine artery, meticulous observation of the relationship between the uterine artery and its branches is crucial for identifying myometrial lesions to facilitate early detection of UAP and minimize misdiagnosis.Keywords: uterine artery, pseudoaneurysm, postpartum hemorrhage, ultrasound, uterine artery embolization